Altruistic Activity as Correctional Treatment - Toch, Hans (International journal of offender therapy and comparative criminology, 2000)
This article discusses activities by prisoners that assist underprivileged persons such as the elderly, children, and the disabled. Among benefits of such involvements for the offenders are a sense of accomplishment, grounded increments in self-esteem, meaningful purposiveness, and obvious restorative implications. Altruistic activity can contribute to cognitive restructuring, especially where opportunities to engage in such behavior are diversified and the experiences and feelings of participants are shared in supportive groups